The Kindness of Strangers: Exploring Interdependencies and Shared Mobilities of Elderly People in Rural Japan - Yamamoto, Fuyo (Jenny) (Social Inclusion, 2017)
For over forty years, most residents in rural areas of Japan have relied on private vehicles to meet their mobility needs. Today, however, the rapid ageing of the population, coupled with low birth rates and migration of young people to urban areas, is posing a variety of new transport challenges. Most notably, the proportion of drivers to non-drivers is getting smaller. This means that non-drivers who relied on family and neighbours for trips in the past, as well as elderly residents who give up their licenses, have fewer people to drive them. Current policy debates tend to focus on technological "solutions", and underestimate the complex social, cultural and inter-personal relationships which underlie transport dependencies in these environments. Using a qualitative semi-structured survey, the current study explores the current mobilities of older people living in a small rural district in Shimane Prefecture, Japan. The resulting analysis reveals how cultural attitudes and social norms affect the ways in which older people manage their mobilities.